On the composite behavior of a rebar truss ribbed slab with incorporated shuttering made of lipped channel section - Favarato, Lucas Fadini (2021)
Composite slabs are high-performant structural elements made of concrete and of structural cold-formed steel sections, mechanically connected to grant the shear transfer between them. Furthermore, they play an important role in design of structures due to the dead load reduction as well as loads into foundations. On account of increased demand for industrialized systems for buildings, composite slabs can produce great impact in reduction of floor depth while spanning longer to meet architectural needs for column-free areas. In this context, a novel system was recently released in the market as an optimized version of the reinforced concrete ribbed slabs, although made of a cold-formed steel lipped channel section as permanent shuttering fastened to a rebar truss through uniformly distributed plastic connectors. Likewise, light filling blocks usually made in Expanded Polystyrene are employed between ribs to reduce dead loads. However, the shear behavior between shuttering and concrete at bottom ribs had not been fully investigated through full-scale experiments, reason why it’s still designed as a non-composite system. Data found in the literature has evidenced fullinteraction between both structural materials when tested with span of 2500 and shear span of 625 (/4), although it’s insufficient to draw a safe conclusion regarding its shear behavior. As such, this research expanded the aforementioned test scope to include extra fourpoint bending tests according to the EN 1994-1-1 (CEN, 2004) with same span of 2500 , however with a larger shear span of 833 (/3). Additionally, reinforced concrete slabs with same dimensions and without the steel shuttering were cast and tested under identical conditions to quantify the formwork contribution to the slab strength. It was observed that the lipped channel steel profile fully interacted with concrete with no end-slips, which has increased the characteristic bending resistance in more than 80% while soaring the ductility in five times when compared to the concrete slabs without the steel shuttering. Finally, seven models found in the literature to calculate the effective moment of inertia were compared with testing results, from which the cracked stiffness approach yielded to best results.